Patient-Reported Outcomes and Knee Mechanics Correlate With Patellofemoral Deep Cartilage UTE-T2* 2 Years After Anterior Cruciate Ligament Reconstruction. Issue 3 (March 2021) - Williams, Ashley A.; Erhart-Hledik, Jennifer C.; Asay, Jessica L.; Mahtani, Gordhan B.; Titchenal, Matthew R.; Lutz, Amelie M.; Andriacchi, Thomas P.; Chu, Constance R.
Background: Patellofemoral joint degeneration and dysfunction after anterior cruciate ligament reconstruction (ACLR) are increasingly recognized as contributors to poor clinical outcomes. Purpose: To determine if greater deep cartilage matrix disruption at 2 years after ACLR, as assessed by elevated patellofemoral magnetic resonance imaging (MRI) ultrashort echo time–enhanced T2* (UTE-T2*), is correlated with (1) worse patient-reported knee function and pain and (2) gait metrics related to patellofemoral tracking and loading, such as greater external rotation of the tibia at heel strike, reduced knee flexion moment (as a surrogate of quadriceps function), and greater knee flexion angle at heel strike. Study Design: Cross-sectional study; Level of evidence, 3. Methods: MRI UTE-T2* relaxation times in patellar and trochlear deep cartilage were compared with patient-reported outcomes and ambulatory gait metrics in 60 patients with ACLR at 2 years after reconstruction. ACLR gait metrics were compared with those of 60 uninjured reference patients matched by age, body mass index, and sex. ACLR UTE-T2* values were compared with those of 20 uninjured reference patients. Results: Higher trochlear UTE-T2* values were associated with worse Knee injury and Osteoarthritis Outcome Scores (KOOS) Sport/Recreation subscale scores (rho = −0.32; P = .015), and showed a trend for association with worse KOOS Pain subscale scores (rho = −0.26; P = .045). At 2 years after ACLR, greater external rotation of the tibia at heel strike was associated with higher patellar UTE-T2* values ( R = 0.40; P = .002); greater knee flexion angle at heel strike was associated with higher trochlear UTE-T2* values (rho = 0.39; P = .002); and greater knee flexion moment showed a trend for association with higher trochlear UTE-T2* values (rho = 0.30; P = .019). Patellar cartilage UTE-T2* values, knee flexion angle at heel strike, and external rotation of the tibia at heel strike were all elevated in ACLR knees as compared with reference knees ( P = .029, .001, and .044, respectively). Conclusion: Patellofemoral deep cartilage matrix disruption, as assessed by MRI UTE-T2*, was associated with reduced sports and recreational function and with gait metrics reflective of altered patellofemoral loading. As such, the findings provide new mechanistic information important to improving clinical outcomes related to patellofemoral dysfunction after ACLR.